2003
DOI: 10.1021/ma030157m
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the α and γ Polymorphs in Random Metallocene−Propylene Copolymers. Effect of Concentration and Type of Comonomer

Abstract: Four sets of random propylene-based copolymers with 1−10 mol % of ethylene, 1-butene, 1-hexene, or 1-octene as co-units, synthesized with the same metallocene catalyst, were investigated by differential scanning calorimetry and wide-angle X-ray scattering following rapid and isothermal crystallization. Parameters related to defect concentration, defect type, and microstructure and thermodynamic and kinetic factors were evaluated as to their role in developing the γ polymorph. The effect of the comonomer in enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
257
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(277 citation statements)
references
References 55 publications
19
257
0
Order By: Relevance
“…[32][33][34] Also, it has been found that the presence of ethylene monomer along the polypropylene chain disturbs the chain regularity and, consequently, decreases polymer crystallization ability; [34][35][36] e.g., its presence decreases crystallinity and linear growth rate and, moreover, induces the formation of the orthorhombic γ-phase. 36,37 However, the effects above have mostly been studied for quiescent crystallization, or under a rheometric flow 35 unable to impose high shear stresses similar to those typically encountered in industrial processing conditions. Here, we focus on the effect of the presence of defects in the molecular architecture on shear-induced crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Also, it has been found that the presence of ethylene monomer along the polypropylene chain disturbs the chain regularity and, consequently, decreases polymer crystallization ability; [34][35][36] e.g., its presence decreases crystallinity and linear growth rate and, moreover, induces the formation of the orthorhombic γ-phase. 36,37 However, the effects above have mostly been studied for quiescent crystallization, or under a rheometric flow 35 unable to impose high shear stresses similar to those typically encountered in industrial processing conditions. Here, we focus on the effect of the presence of defects in the molecular architecture on shear-induced crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…can crystallize into the c phase from melt, which is favored by high crystallization temperature or slow cooling rate due to kinetic limitation. [10][11][12] Unlike a form, the chain packing in the orthorhombic unit cell of c phase is nonparallel. Instead, the direction of the chain axis in adjacent bilayers is tilted by approximately 80 against each other and approximately 40…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is consistent with other authors that reported the similarity between isotactic polypropylene and polybutene conformations, which facilitates the inclusion of 1-butene in the iPP crystal structure. [35][36][37][38][39][40] Ethylene comonomer, due to its small size, is not excluded from the crystal lattice, but it interrupts the iPP helix, shortening the crystal sequence and incorporating these distorted sequences to the amorphous fraction of the polymer. [37,41,42] Figure 1a also shows the totally amorphous profile, amPP, of an elastomeric PP sample [30] , in this case scaled to account for the amorphous component corresponding to the terpolymer.…”
Section: Experimental Partmentioning
confidence: 99%
“…Polypropylene produced with a Ziegler Natta catalyst has a broad distribution of defects from chain to chain and a distribution of defects intramolecularly that deviates strongly from the random behavior: the defects are more concentrated in the molecules with lower molar mass [36]. Since the presence of short isotactic sequences is a requirement for the formation of the γ polymorph, it is not surprising that ZN iPP homopolymer leads to insignificant contents of crystallites of the γ form, contrary to the case of iPP synthesized with a metallocene catalyst with the same overall concentration of defects.…”
Section: 1 Samples With Q and S Treatmentmentioning
confidence: 99%